Bacteremia due to a VIM-1 Producing Klebsiella Pneumoniae Isolate from an Acute Lymphoblastic Leukemia Patient in Antalya - Sepin Ozen, Nevgun; Ogunc, Dilara; Ongut, Gozde; Seyman, Derya; Daglar, Duygu; Ozhak Baysan, Betil; Colak, Dilek; Hazar, Volkan; Naas, Thierry (Annals of Medical Research, 2021)
None